EXTREME PROGRAMMING SEBAGAI METODE PENGEMBANGAN E-KEUANGAN PADA PONDOK PESANTREN QODRATULLAH - Oktaviani, Nia; Hutrianto, Hutrianto (Universitas Bina Darma, 2016)
Abstract: Pondok Pesantren Qodratullah founded in 1972 is located Langkan vilage. Guiding and structuring continue to be developed with the reform in the field of education, methodology, development of infrastructure and expand the functions of the cottage as a faith-based educational institutions and public. Student who learn from different regions, namely South Sumatra, Aceh, North Sumatra, Riau, West Sumatra, Jambi, Bengkulu, Lampung and Jakarta. With a diverse area of origin of students, as well as the many activities in addition to education, the financial management of the students and the cottage needs to be improved. Therefore in this study have been developed e-finance using Extreme Programmimg. Where in the e-finance have a payment feature, the financial statements and reports arrears in payment of fees. E-finance has also been tested with a black box approach that states all the functional software running well. Kata kunci: E-finance, Qodratullah, Extreme Programming